Motor and Visual-spatial Cognitive Abilities in Children Treated for Infantile Esotropia. Issue 4 (August 2021) - Dillmann, Julia; Freitag, Claudia; Lorenz, Birgit; Holve, Kerstin; Schweinfurth, Silke; Schwarzer, Gudrun
While many studies have investigated links between motor and visual spatial cognitive abilities in typically developing children, only a few studies have tested this link among children with innate handicaps. Therefore, we assessed motor abilities (using the M-ABC-2) and visual spatial cognitive skills (using the Block Design subtest of the WPPSI-III and a picture mental rotation task, PRT) of 5-7 year old typically developing children (n= 17) and same-aged children with severe deficits in stereopsis due to infantile esotropia (n= 17). Compared to the typically developing children, children with esotropia showed significantly poorer motor performances, especially in manual dexterity and ball skills, and significantly poorer and slower performance on the visual spatial cognitive tasks. Especially the girls treated for infantile esotropia needed more time to mentally rotate the pictures of the PRT correctly. Overall, this study showed that perceptual, motor and cognitive processes are interconnected and that children treated for infantile esotropia had an increased risk of motor and visual spatial cognitive deficits.